Polysaccharide Fibers as Matrices for Solid-Surface Fluorescence. (8th December 2014) - Rogacheva, Svetlana M.; Shipovskaya, Anna B.; Strashko, Anna V.; Gubina, Tamara I.; Volkova, Elena V.; Melnikov, Andrey G.
Abstract : Fibers of cellulose diacetate (CDA) and chitosan (CTS) of polycationic and polybasic forms were tested as matrices for solid-surface fluorescence (SSF) of several fluorescent probes—eosin Y, trypaflavine, and pyrene. The morphology and surface potential of these matrices were examined. The influence of structural and energetic characteristics of the fibrous polysaccharide materials at SSF of the probes was shown. Fluorescence was studied in aqueous solutions of eosin Y and trypaflavine, in water-ethanolic and water-micellar surfactant media of pyrene, before and after dynamic sorption of the dyes on fibers and in the adsorbed state. The surface of CDA fiber was shown to be capable of sorbing trypaflavine from water and pyrene from water-micellar surfactant media of various types, so it can be a promising matrix for SSF of pyrene and trypaflavine and their chemical analogs. The Coulomb interactions were proposed to determine eosin Y and trypaflavine concentration on the surface of CTS matrices and the SSF of these probes. The CTS fibers were permeable to hydrophobic pyrene dissolved in an ethanol-water medium or solubilized in the micelles of ionic surfactants.